Mechanisms regulating phosphatase specificity and the removal of individual phosphorylation sites during mitotic exit. (15th July 2016) - Rogers, Samuel; McCloy, Rachael; Watkins, D Neil; Burgess, Andrew
Abstract : Entry into mitosis is driven by the activity of kinases, which phosphorylate over 7000 proteins on multiple sites. For cells to exit mitosis and segregate their genome correctly, these phosphorylations must be removed in a specific temporal order. This raises a critical and important question: how are specific phosphorylation sites on an individual protein removed? Traditionally, the temporal order of dephosphorylation was attributed to decreasing kinase activity. However, recent evidence in human cells has identified unique patterns of dephosphorylation during mammalian mitotic exit that cannot be fully explained by the loss of kinase activity. This suggests that specificity is determined in part by phosphatases. In this review, we explore how the physicochemical properties of an individual phosphosite and its surrounding amino acids can affect interactions with a phosphatase. These positive and negative interactions in turn help determine the specific pattern of dephosphorylation required for correct mitotic exit. Abstract : During mitotic exit, phosphatases reverse thousands of phosphorylation events in a specific temporal order to ensure that cell division occurs correctly. This review explores how the physicochemical properties of the phosphosite and surrounding amino acids affect interactions with phosphatase/s and help determine the dephosphorylation of individual phosphorylation sites during mitotic exit.